Azobenzene derivatives show anti-cancer activity against pancreatic cancer cells only under nutrient starvation conditions via G0/G1 cell cycle arrest. (9th April 2021) - Shinzawa, Kenta; Kageta, Daiki; Nash, Robert J.; Fleet, George W.J.; Imahori, Tatsushi; Kato, Atsushi
Abstract: Pancreatic cancer is one of the most aggressive cancers with a poor prognosis. Previous studies suggested that nutrient-deprived conditions may play a critical role in pancreatic cancer cell survival and resistance to chemotherapy. We describe a novel series of azobenzene derivatives including (E) -1-(4-methyl-3-((2-methyl-5-(naphthalen-1-yl)phenyl)diazenyl)phenyl)naphthalen-2-ol (9 ) with efficacy and selectivity in nutrient-deprived conditions. Although anticancer drug 5-fluorouracil (5-FU) was ineffective under nutrient-deprived conditions, five of our designed compounds, 9 and four other related compounds 11 –14, showed anticancer activity with IC50 values ranging from 1.5 to 9.6 μM. Interestingly, only 9 showed no cytotoxicity in normal conditions. This selectivity profile of 9 is clearly opposite to that of 5-FU. Furthermore, cell cycle analysis showed that, in contrast to S phase arrest induced by 5-FU, 9 caused G0 /G1 phase arrest, which might block cancer cell growth by arresting them in quiescence. Therefore, it could be a novel and promising candidate for effective pancreatic cancer treatment under nutrient-deprived conditions. Graphical abstract: Image 1 Highlights: Nutrient-deprived conditions (NDC) may play a critical role in pancreatic cancer cell survival and resistance to chemotherapy. Syntheses of a series of azobenzene derivatives including (9 ) are described. 5 Azo derivatives showed anticancer activity with IC50 values ranging from 1.5 to 9.6 μM with efficacy and selectivity in NDC. In contrast anticancer drug 5-fluorouracil (5-FU) was ineffective under NDC. Only 9 showed no cytotoxicity in normal conditions. Cell cycle analysis showed that, in contrast to S phase arrest induced by 5-FU, 9 caused G0 /G1 phase arrest.